2013
DOI: 10.1097/aap.0b013e31827049c6
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Ondansetron Does Not Prevent Shivering or Decrease Shivering Severity During Cesarean Delivery Under Combined Spinal Epidural Anesthesia

Abstract: Intravenous ondansetron 8 mg before performing CSE anesthesia in women undergoing elective cesarean delivery does not decrease the incidence or severity of shivering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 23 publications
1
41
3
Order By: Relevance
“…The dosage of ondansetron was either 4 mg or 8 mg in individual study, and meperidine was 0.4 mg/kg in all the three studies [13,15,18]. The trial drugs were all given before anesthesia, but one [17] at the end of the surgery.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The dosage of ondansetron was either 4 mg or 8 mg in individual study, and meperidine was 0.4 mg/kg in all the three studies [13,15,18]. The trial drugs were all given before anesthesia, but one [17] at the end of the surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Study by Browning et al [17], which found ondansetron could not reduce the incidence of shivering, contributed to the heterogeneity as identified by forest plots and sensitive analysis. The subgroup analysis also confirmed the source of the heterogeneity was from the study (data not show).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies indicate the role of serotonin receptors in thermoregulation at different levels. Nevertheless, some studies have reported that ondansetron did not change the threshold of shivering and probably reduces shivering thorough the central effects and ondansetron does not decrease the incidence or severity of shivering in women undergoing elective cesarean delivery (17, 18). Although 0.4 mg/kg of meperidine rarely causes unwanted cardiovascular effects, it may cause respiratory depression, particularly when used with other opioids.…”
Section: Discussionmentioning
confidence: 99%